Microbial Communities Associated With Stable Fly (Diptera: Muscidae) Larvae and Their Developmental Substrates. (11th January 2017) - Scully, Erin; Friesen, Kristina; Wienhold, Brian; Durso, Lisa M.
Abstract : Bacteria are essential for stable fly ( Stomoxys calcitrans (L.)) larval survival and development, but little is known about the innate microbial communities of stable flies, and it is not known if their varied dietary substrates influence their gut microbial communities. This investigation utilized 454 sequencing of 16S and 18S amplicons to characterize and compare the bacterial and eukaryotic microbial communities in stable fly larvae and their developmental substrates. The microbial community of the third-instar stable fly larvae is unambiguously distinct from the microbial community of the supporting substrate, with bacterial communities from larvae reared on different substrates more similar to each other than to the communities from their individual supporting substrates. Bacterial genera that were more abundant proportionally in larvae compared to their substrates were Erysipelothrix, Dysgonomonas, Ignatzschineria (Gammaproteobacteria), and Campylobacter (Epsilonprotobacteria). The alphaproteobacteria Devosia, Brevundimonas, Sphingopyxix, and Paracoccus were more abundant proportionally in field substrates compared to their larvae. The main genera responsible for differences between the positive and negative field substrates were Dysgonomonas and Proteiniphilum . In contrast to Dysgonomonas, Proteiniphilum was more abundant in substrate than in the larvae. A large number of sequences were assigned to an unclassified protest of the superphylum Alveolata in larvae and their substrate. Microscopy validated these findings and a previously undescribed gregarine (phylum Apicomplexa, class Conoidasida) was identified in stable fly larvae and adults.